2017
DOI: 10.1016/j.addr.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Xenobiotic transporters and kidney injury

Abstract: Renal proximal tubules are targets for toxicity due in part to the expression of transporters that mediate the secretion and reabsorption of xenobiotics. Alterations in transporter expression and/or function can enhance the accumulation of toxicants and sensitize the kidneys to injury. This can be observed when xenobiotic uptake by carrier proteins is increased or efflux of toxicants and their metabolites is reduced. Nephrotoxic chemicals include environmental contaminants (halogenated hydrocarbon solvents, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(85 citation statements)
references
References 254 publications
(265 reference statements)
2
80
0
3
Order By: Relevance
“…These morphological alterations were a clear index of renal tubular injury. The proximal tubules showed the greater damage; it is not surprising because they are the major sites of accumulation of xenobiotics, as a result they fulfil the hard function to absorb and excrete the toxic substances.…”
Section: Discussionmentioning
confidence: 99%
“…These morphological alterations were a clear index of renal tubular injury. The proximal tubules showed the greater damage; it is not surprising because they are the major sites of accumulation of xenobiotics, as a result they fulfil the hard function to absorb and excrete the toxic substances.…”
Section: Discussionmentioning
confidence: 99%
“…Drug-induced nephrotoxicity is a major problem in clinical human therapy since the use of nephrotoxic drugs is often unavoidable. Thus, the prediction of drug nephrotoxicity appears of particular relevance in order to avoid kidney injury and/or perturbation of pharmacokinetic drug properties that are closely related to kidney excretion [14]. Moreover, the possibility to optimise drug design by using a functional screening in vitro model represents an interesting tool for the characterization of drug toxicity and/or for the development of news drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Computational modeling suggests that As binds to free thiols on the MT molecule [79,80], which may reduce the oxidative injury induced by exposure to As [81]. Interestingly, it has been suggested that the formation of MT-As complexes does not occur following acute exposure to iAs; rather, it was postulated that these complexes are formed only in cases of chronic exposure [82].…”
Section: Environmentally Relevant Toxic Metalsmentioning
confidence: 99%